Efficacy of a topical herbal and mineral formulation (Dynamiclear) for the treatment of herpes simplex labialis in the community setting: study protocol for a randomised, double-blind placebo-controlled trial. Issue 1 (12th January 2020) - Armour, Mike; Semprini, Alex; Ee, Carolyn; MacCullagh, Lois; Shortt, Nick
Abstract : Introduction: Herpes simplex labialis (HSL) is a common infection that can cause painful lesions on the oral mucosa, commonly referred to as cold sores. Current biomedical treatments include topical aciclovir, which reduces the episode duration by an average of 0.5 days. This study will examine the efficacy and tolerability of an over-the-counter topical treatment, Dynamiclear in reducing duration and severity of HSL episodes. Methods and analysis: This prospective, randomised, double-blind, placebo-controlled, multi-centre trial will recruit a minimum of 292 adult participants across Australia and New Zealand who present with a cold sore within 48 hours of onset. They will be randomly allocated in a 2:1 ratio to receive either topical Dynamiclear (active) or placebo. Dynamiclear's active ingredients are Hypericum perforatum, Calendula Officinalis and copper sulfate. A single topical treatment of active or placebo will be applied by a pharmacy-based investigator, and participants will be provided with a viral swab kit to confirm presence of herpes virus 1 or 2 from ulcerated lesions. Participants will receive reminders by email and/or SMS to complete an online daily diary assessing their cold sore lesion using a visual guide, and recording other symptoms on numeric scales until healed. The primary outcome variable is median duration of HSL episode in days (participant evaluated) from presentation to return to normal skin. Secondary outcomes include severity of lesion pain, itching, burning and tingling during the symptomatic phase and proportion of lesions progressing to ulceration. Ethics and dissemination: Australian ethics approval from Western Sydney University Human Research Ethics Committee, ref: H12776. New Zealand Ethics approval from The Health and Disability Ethics Committees (HDEC) ref: 18/CEN/151. Results will be published in a peer-reviewed academic journal, presented at academic meetings and reported to participants Trial registration numbers: Australia and New Zealand Clinical Trials Registry (ACTRN12618000890235); Universal Trial Number (UTN) (U1111-1233-2426).